ANALISIS SENTIMEN PENILAIAN MASYARAKAT INDONESIA TERHADAP KONFERENSI G20 DI BALI DENGAN MENGGUNAKAN METODE NAIVE BAYES - Windy Kusumawati Suhet; Adi Nugroho (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Lot of Indonesian people support the holding of the G20 conference in Bali and many people also disagree with the G20 that will held/hold in Bali for various reasons. Therefore this research is conducted to find out how much the Indonesian people agree or disagree with the holding of the G20 High-Level Conference (Summit) which was held in Bali, Indonesia. In this study used research methods of data collection, preprocessing stage, Naive Bayes classification stage, and confusion matrix evaluation stage. In this study, 2,255 data were used with 1,000 training data and 1,255 test data. After the data is processed and the sentiment predicted in the test data, the confusion matrix is calculated to calculate the accuracy of the results. On data that has been processed the accuracy obtained is 95.60%.